Hypoxia and hypoxia-inducible factors in diabetes and its complications - Catrina, Sergiu-Bogdan; Zheng, Xiaowei (Diabetologia, 2021)
Hypoxia-inducible factors (HIFs) are the key regulators of oxygen homeostasis in response to hypoxia. In diabetes, multiple tissues are hypoxic but adaptive responses to hypoxia are impaired due to insufficient activation of HIF signalling, which results from inhibition of HIF-1α stability and function due to hyperglycaemia and elevated fatty acid levels. In this review, we will summarise and discuss current findings about the regulation of HIF signalling in diabetes and the pathogenic roles of hypoxia and dysregulated HIF signalling in the development of diabetes and its complications. The therapeutic potential of targeting HIF signalling for the prevention and treatment of diabetes and related complications is also discussed. Graphical abstract